Investigating the Use of Formative Assessment in Improving Student Learning Outcomes in Mathematics - Morten Misfeldt; Helle Alro; Dorthe Berntsen (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study investigates the use of formative assessments in improving student learning outcomes in mathematics. The research focuses on how regular, low-stakes assessments help teachers identify student misconceptions, provide timely feedback, and tailor instruction to meet students' needs. The study finds that formative assessments lead to higher student performance, particularly in understanding complex mathematical concepts. The paper explores various formative assessment techniques, such as quizzes, peer reviews, and self-assessments, and their effectiveness in fostering student learning and achievement in mathematics.